KEPUASAN PELANGGAN DI PENGARUHI OLEH PROMOSI MELALUI KUALITAS LAYANAN DI SHOPPE FOOD KOTA BEKASI - Romero Fabio Ariyanto; Edy Sanusi Silitonga (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2024)
The research objective to be achieved is to determine the effect of promotion on consumer satisfaction at food shops in Bekasi City through service quality. This research uses quantitative methods. The population in this research is food shop consumers in Bekasi City. By using the Slovin formula. The technique used for sampling is simple random sampling. The data analysis method uses path analysis. The research results can be concluded as follows: Promotion has a significant direct effect on consumer satisfaction, service quality has a significant direct effect on consumer satisfaction, promotion has a significant direct effect on service quality, and promotion has a positive and significant indirect effect on consumer satisfaction at food shops in Bekasi City through service quality.